Analisis Faktor dan Indikator yang Memengaruhi Kinerja Manajemen Waste Konstruksi pada Proyek Bangunan Gedung Komersial - I Made Swasnawa; I Putu Artama Wiguna (LPPM Institut Pendidikan Nusantara Global, 2026)
The rapid growth of commercial building development in Bali Province has led to increased construction activities and a higher potential for construction waste generation, while the implementation of construction waste management during the project execution phase remains insufficiently integrated. Although various construction waste management performance indicators have been proposed in previous studies, empirical validation of the underlying factors and indicators using structural equation modeling (SEM), particularly in the context of commercial building projects, remains limited. This study aims to identify and validate the key indicators determining construction waste management performance in commercial building projects in Bali Province. Data were collected through a questionnaire survey and analyzed using partial least squares structural equation modeling. The results confirm 21 valid indicators representing four key performance-determining variables. The findings indicate that construction methods, policies and governance, design and documentation, as well as material and equipment management have a significant influence on construction waste management performance. Among these variables, reducing unnecessary activities (outer loading = 0.817), supervision of construction activities (0.860), design errors (0.851), and warehouse capacity (0.841) were identified as the most representative indicators for their respective constructs, as reflected by the highest outer loading values. This study provides empirical contributions to the development of construction waste management performance indicators and offers practical implications for improving waste management performance in commercial building projects.